National Identity, Nationalism and Constitutional Change
XI, 211 p. 3 illus.
Keywords: What does it mean to say you're English, Scottish, British? Does it matter much to people? Has devolution and constitutional change made a difference to national identity? Does the future of the UK depend on whether or not people think they are British? Social and political scientists answer these questions vital to the future of the British state.